2004
DOI: 10.1161/01.cir.0000148780.36121.47
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Metalloproteinases 2/9 in Epidermal Growth Factor Receptor Transactivation in Pressure-Induced Myogenic Tone in Mouse Mesenteric Resistance Arteries

Abstract: Background-Epidermal growth factor receptor (EGFR) transactivation is a mediator of angiotensin II (Ang II) signaling in cultured vascular smooth muscle cells isolated from large arteries. The present study used mouse mesenteric resistance arteries (MRAs) to investigate the role of EGFR transactivation under pressure-induced myogenic tone (MT). Methods and Results-Isolated MRAs were mounted in an arteriograph and stimulated by 25 to 125 mm Hg or with Ang II and KCl. Stepwise increases in pressure resulted in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
95
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 37 publications
9
95
0
Order By: Relevance
“…Other aspects of MMP involvement to facilitate migration may also occur. For example, release of extracellular pro-migratory cytokines including heparin-bound EGF [24] and TNFα [25] by metalloproteinase activation has been reported in some systems.…”
Section: Discussionmentioning
confidence: 99%
“…Other aspects of MMP involvement to facilitate migration may also occur. For example, release of extracellular pro-migratory cytokines including heparin-bound EGF [24] and TNFα [25] by metalloproteinase activation has been reported in some systems.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cisPt was also able to inhibit PC E1Araf cells motility (Fig 4.A), and the administration of MMP-2 active protein to cisPt-treated cells restored such motility, further suggesting that in the cisPt-induced decrease of cell migration MMP-2 is involved (Fig 4.C). MMPs are able to modulate several signalling pathways; for example, MMP-2, MMP-7 and MMP-9 can cleave cell surface pro-HB-EGF and liberate the soluble active growth factor [31]. MMPs can also modulate apoptosis by cleaving death ligands (TNF-alpha and FasL) and their receptors that trigger apoptosis by acting in an autocrine or paracrine manner [32].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that activation of ADAM12 (8) or ADAM17 (22) could induce the release of HB-EGF and subsequent EGFR phosphorylation, which may eventually lead to cardiomyocyte hypertrophy, while inhibition of ADAM12 or administration of an HB-EGF neutralizing antibody blocked GPCR agonist-stimulated myocyte hypertrophy (8). A study performed by Lucchesi et al supported the existence of a signaling pathway for pressure-induced HB-EGF release and subsequent EGFR activation in murine mesenteric resistance arteries (20). Zhang et al confirmed that a similar pathway is activated to promote smooth muscle cell growth (32).…”
Section: Fig 5 Atorvastatin Inhibited the Egfr-erk Signaling Pathwamentioning
confidence: 96%
“…Recent studies have revealed that the activation of MMP2 and MMP9 (20), or MMP3 (21), or ADAM12 (8) and ADAM17 (22,23) can induce the release of HB-EGF and subsequent EGFR transactivation, while upregulation of the expression of MMPs is reported to be associated with cardiac remodeling (24,25). In addition, statins are reported to effectively inhibit the activity of MMPs (26,27).…”
Section: Atorvastatin Downregulates Expression Of Mmps and Hb-egf Andmentioning
confidence: 99%
See 1 more Smart Citation